Aplikasi Model RASCH dalam Pengujian Alat Ukur Kesehatan Mental di Tempat Kerja - Aziz, Rahmat (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2015)
This research aims to examine the validity and reliability of mental health scale in the workplace by using the Rasch model approach as well as compare the results of analysis with classical test theory approach. The subject were 60 employees at the State Islamic University Malang. The analysis showed that the mental health scale in the workplace is declared valid and reliable either by using the approach of Rasch model and classical test theory. This means that both approaches are able to find the same results on the test of mental health scale in the workplace.